Constitutional Values and Restorative Justice: A Critical Analysis in the Indonesian Context - Rinda Philona; Awaludin, Awaludin (KARSA Journal of Social and Islamic Culture, 2025)
This research examines the alignment between Restorative Justice concepts and constitutional principles embedded in Indonesia’s 1945 Constitution, analyzing its effectiveness in achieving substantive justice and social restoration. Employing normative legal research methodology with statute, conceptual, comparative, and case approaches, this study investigates how Restorative Justice can serve as an instrument for actualizing constitutional values within Indonesia's constitutional system. The research reveals profound philosophical harmonization between Restorative Justice principles and constitutional values, particularly regarding human rights protection (Article 28I), substantive justice (Article 28D), and the rule of law principle (Article 1(3)). The analysis demonstrates that Restorative Justice effectively achieves substantive justice through participatory processes that prioritize dialogue, accountability, and community involvement over punitive measures. Evidence from juvenile criminal justice implementation and comparative analysis with international practices indicates significant effectiveness in reducing recidivism rates and strengthening social cohesion. The study concludes that Restorative Justice constitutes a constitutional imperative rather than merely an alternative judicial mechanism, representing the actualization of substantive constitutionalism that aligns with Indonesia’s foundational Pancasila values. This research contributes to constitutional law scholarship by establishing a theoretical framework that integrates alternative justice mechanisms within constitutional governance, providing empirical evidence for constitutional-based Restorative Justice effectiveness, and offering methodological foundations for future research examining the intersection between constitutional values and innovative justice practices.